School Digital Education and Training Management Relationships in Order to Improve Teacher Literacy Skills During the Pandemic - Monovatra Predy Rezky; Joko Sutarto; Titi Prihatin; Arief Yulianto (Universitas Negeri Semarang, 2021)
Modification of the current Education management in learning activities has increased so rapidly. The integration of information technology into learning procedures has become a necessity that must be tried in order to accommodate curriculum requirements and the spirit of changing times. Learning activities are no longer limited to the context of space and time that take place in conventional learning management, but in this 4.0 revolution period, virtual or online activities are becoming a trend. Teacher training is no exception, which today is a demand for teacher professional development in terms of mastering technology. Especially during the pandemic, it is almost so difficult for teachers to develop themselves by participating in several trainings without technological skills. The public junior high school teachers in North Konawe are proof that technology is being used and utilized. The results of descriptive analysis show that there is a difference in the average pretest and posttest of the training participants with a pretest value of 66.43 with a standard deviation of 5.37 and a posttest value of 81.22 with a standard deviation of 6.00, then correlation analysis with the paired sample t test shows a correlation value. its value is 0.715 with sig = 0.00 < = 0.05 which means that the results of the pretest and posttest before being used and after being used by the management have a positive and significant correlation.